THE PLACE OF VIRTUAL COMMUNITIES IN SCIENTIFIC RESEARCH PUBLIC COMMUNICATIONS - PAZDERSKA, RUSLANA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article focuses on the study of public communications as an integral part of the analysis of virtual communities. Accordingly, the definition of a "virtual community" has been formulated as a community in which information is regularly published about a specific industry where users from different backgrounds can communicate. The main task of the work is substantiated, which is to study the directions of development of public communications, combining different types of specializations of human activity. Given the study of which information technologies of virtual communities can be used. The relationship between the directions is schematically presented. The first area to be studied is organizational and legal research. It is characterized by the introduction of structure management tools in accordance with legal norms in the organization of all processes. The specifics of its areas are reviewed: personnel management, leadership in the way of communication, corporate equality policy. Second, sociological research, the purpose of such research is to find effective ways to solve society's problems by obtaining the necessary knowledge. This includes the following areas: public relations, family interactions, types of thinking and human behavior, behavioral and situational strategies. The latter reviewed the direction of information and communication research. Since the rapid development of various areas of human activity in relation to information technology allows us to witness the automation of many processes. It includes such sub-processes as ontological data analysis (an example of ontology is presented) and the relevance of development. As a result, the conclusions about the work done are substantiated. Namely, by combining the principles laid down in the specifics of communities of practice and thematic virtual communities, it is possible not only to change the opinion about the negative impact of virtual communities, but also to improve the organization of their use by users.
Keywords: public communications; directions; virtual communities; research; organizational and legal; sociological and information and communication